2019
DOI: 10.1021/acsami.9b03879
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Thermal Catalytic Enhancement in Doped MnO2–Au Nano-Heterojunctions

Abstract: Sodium (Na)- and potassium (K)-doped δ-MnO2, which presented different band gaps, were synthesized by a hydrothermal method. Then, uniform Au nanoparticles (NPs) were deposited on MnO2 to form metal–semiconductor nano-heterojunctions (MnO2–Au). By comparing their temperature-dependent thermal catalytic performances, p-aminothiophenol to p,p′-dimercaptoazobenzene conversion was used as proof-of-concept transformations. MnO2–Au hybrid materials demonstrated better thermal catalytic performances relative to indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 70 publications
3
23
0
1
Order By: Relevance
“…The band gap for the Mg-doped MnO 2 nanoflowers was calculated as 1.13 eV from the UV-VIS spectrum shown in Supplementary Figure S3A. The narrower bandgap observed here relative to the previously reported (Sakai et al, 2005;John et al, 2016) might be attributed to the doping of Mg 2+ ions between layers of MnO 2 (Luo et al, 2000;Wang et al, 2017;Hu et al, 2019;Zhu et al, 2019), which will be discussed later.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…The band gap for the Mg-doped MnO 2 nanoflowers was calculated as 1.13 eV from the UV-VIS spectrum shown in Supplementary Figure S3A. The narrower bandgap observed here relative to the previously reported (Sakai et al, 2005;John et al, 2016) might be attributed to the doping of Mg 2+ ions between layers of MnO 2 (Luo et al, 2000;Wang et al, 2017;Hu et al, 2019;Zhu et al, 2019), which will be discussed later.…”
Section: Resultsmentioning
confidence: 47%
“…We regarded I Mn and I K as the Mn and K intensities from one Mn and K atom, respectively. The total intensities of Mn 2p 3/2 and K 2p 3/2 can be expressed by following expression (Hu et al, 2019;Zhu et al, 2019):…”
Section: The Calculation Of Atomic Ratiosmentioning
confidence: 99%
“…j) Reproduced with permission. [ 305 ] Copyright 2019, American Chemistry Society. k) Schematic illustration of the fabrication route of MnO 2 /PANI.…”
Section: Fabrication Of Mno2‐based Compositesmentioning
confidence: 99%
“…uniformly loaded Au on the surface of MnO 2 nanoflowers and obtained Au/MnO 2 metal–semiconductor nano‐heterojunctions (Figure 17j). [ 305,306 ] They found that Au/MnO 2 heterojunctions showed better thermal catalytic performances compared to individual Au NPs. This can be ascribed to the transfer of thermally excited electrons from MnO 2 to Au NPs, which increases the electron density, thus helping to improve the thermal catalytic performance.…”
Section: Fabrication Of Mno2‐based Compositesmentioning
confidence: 99%
“…While potassium tantalates exhibit excellent stability in photocatalysis, their absorption locates at Ultra-violet (UV) range and limits the employment of visible light. In order to make use of solar energy with higher efficiency, various methods are explored to modify potassium tantalates, such as cations doping [11,12] and construction of hetero-structure [13,14]. For instance, porphyrin was used as mixing dyes to sensitize potassium tantalates for photo-splitting water to H 2 or O 2 [8].…”
Section: Introductionmentioning
confidence: 99%